2022
DOI: 10.3390/nano12234142
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticles in Chemical EOR: A Review on Flooding Tests

Abstract: The use of nanofluids is showing promise as an enhanced oil recovery (EOR) method. Several reviews have been published focusing on the main mechanisms involved in the process. This new study, unlike previous works, aims to collect information about the most promising nano-EOR methods according to their performance in core-flooding tests. As its main contribution, it presents useful information for researchers interested in experimental application of nano-EOR methods. Additional recoveries (after brine floodin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 109 publications
(161 reference statements)
0
6
0
Order By: Relevance
“…For the purpose of removing oil films from the surface of rocks, various kinds of nanoparticles, including metal oxides and organic (dendrimers and biopolymers), inorganic, and composite particles, have been experimented. 61 Research has shown that nanoparticles derived from the oxides of metals (Al 2 O 3 , CuO, TiO 2 , and Fe 2 O 3 ) can lower the oil/water IFT and also give rise to the disjoining pressure that pushes toward the solid surface and oil−water interface. 62 IFT is reduced as nanoparticles separate out at the oil−water contact from the aqueous phase.…”
Section: Methods Of Enhancing Stability Of Nanofluid Dispersionsmentioning
confidence: 99%
“…For the purpose of removing oil films from the surface of rocks, various kinds of nanoparticles, including metal oxides and organic (dendrimers and biopolymers), inorganic, and composite particles, have been experimented. 61 Research has shown that nanoparticles derived from the oxides of metals (Al 2 O 3 , CuO, TiO 2 , and Fe 2 O 3 ) can lower the oil/water IFT and also give rise to the disjoining pressure that pushes toward the solid surface and oil−water interface. 62 IFT is reduced as nanoparticles separate out at the oil−water contact from the aqueous phase.…”
Section: Methods Of Enhancing Stability Of Nanofluid Dispersionsmentioning
confidence: 99%
“…These field trials demonstrate that nano-EOR has the potential to be a viable technology for improving oil recovery in a variety of reservoir conditions. 29,138 6.2. Laboratory Tests and Field Performance.…”
Section: Major Nano-eor Field Trialsmentioning
confidence: 99%
“…(iii) ConocoPhillips’ field trial in the United States: This field trial demonstrated that nano-EOR can be used to improve oil recovery from mature reservoirs. These field trials demonstrate that nano-EOR has the potential to be a viable technology for improving oil recovery in a variety of reservoir conditions. , …”
Section: Aspects Of the Fieldmentioning
confidence: 99%
“…The emergence and extensive applications of nanotechnology in diverse industries such as electronics, biomedicine, pharmaceuticals, materials, aerospace, and more have prompted many experts in energy-related fields to invest in this technology [5]. Consequently, numerous researchers have turned to the use of nanoparticles to address various challenges within the oil industry, enhance the efficiency of conventional EOR methods, and increase production from oil reservoirs, particularly heavy and extraheavy oil reservoirs [6,7]. Nanotechnology deals with materials at dimensions exceedingly close to the molecular scale (nanometers, 10-9 m).…”
Section: Introductionmentioning
confidence: 99%